HDAC6 Deacetylates and Ubiquitinates MSH2 to Maintain Proper Levels of MutSα - Zhang, Mu; Xiang, Shengyan; Joo, Heui-Yun; Wang, Lei; Williams, Kendra A.; Liu, Wei; Hu, Chen; Tong, Dan; Haakenson, Joshua; Wang, Chuangui; Zhang, Shengping; Pavlovicz, Ryan E.; et al. (Molecular cell, 2014)
MutS protein homolog 2 (MSH2) is a key DNA mismatch repair protein. It forms the MSH2-MSH6 (MutSα) and MSH2-MSH3 (MutSβ) heterodimers, which help to ensure genomic integrity. MutSα not only recognizes and repairs mismatched nucleotides but also recognizes DNA adducts induced by DNA-damaging agents, and triggers cell-cycle arrest and apoptosis. Loss or depletion of MutSα from cells leads to microsatellite instability (MSI) and resistance to DNA damage. Although the level of MutSα can be reduced by the ubiquitin-proteasome pathway, the detailed mechanisms of this regulation remain elusive. Here we report that histone deacetylase 6 (HDAC6) sequentially deacetylates and ubiquitinates MSH2, leading to MSH2 degradation. In addition, HDAC6 significantly reduces cellular sensitivity to DNA-damaging agents and decreases cellular DNA mismatch repair activities by downregulation of MSH2. Overall, these findings reveal a mechanism by which proper levels of MutSα are maintained. [Display omitted] •HDAC6 harbors intrinsic ubiquitin E3 ligase activity•HDAC6 sequentially deacetylates and ubiquitinates MSH2 for degradation•HDAC6 increases cellular tolerance to DNA damage•HDAC6 decreases DNA mismatch repair activities The level of MutSα, a heterodimer of MSH2 and MSH6, governs DNA damage response and DNA mismatch repair (MMR) activities. Here, Zhang et al. show that HDAC6 can both deacetylate and ubiquitinate MSH2 to attenuate mismatch repair, which is particularly important in the context of DNA damage that can lead to futile cycles of mismatch repair.